Are there neurological symptoms in the type 1of Gaucher disease? - alai, mohammad reza; Jafari, Narjes (Iranian Journal of Child Neurology, 2018)
objective Gaucher disease is the most common of the inborn error of metabolic disorder that known as lipid storage disorders. This disorder is caused by a deficiency of the enzyme glucocerebrosidase. .There for , glucocerebroside accumulate in multiple organs. Symptoms may begin at any age ( in early life until the adulthood )and include skeletal disorders, organomegally , and cytopenia. Gaucher disease is classified into three types. type 1 is the most common form and named non neuropatic form . Type 2 is named acute infantile neuropathic form,because severe neurological symptoms are apparent by 3 months of age. Type 3 is named chronic neuropathic form. Videlicet,this disorder is classified on the presence or absence of neurological symptoms . Material and methods In this study , We assesed neurological symptoms in our GD1patients and compared them with GD3 patients. Three patients with GD3 and eight patients with GD1 entered in this study. Result We found in this study that patients with GD1 had neurological problems including: Cognitive impairment,developmental disability ,behavioral disorder, microcephaly ,increased DTR,too. Though,some symptoms including :seizure,supranuclear gaze palsy, cerebellar sign and ataxia only excist in GD3 patients . conclusion In previous studies has mentioned that distinction between type 1 and 3 is by neurological symptoms but we found some neurological signs are seen in Type 1,too. Although, the neurological symptoms are most severe in type 3 and some symtoms only detected in GD3 . So, generally neurological symptoms alone can not differentiate the types of gauche disease.